Giving a voice and holding to account: a critical civic and democratic discourse analysis of The Big Debate South Africa TV show's opportunities for 'Political Listening' - Mgqoboka, Banathi (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
The television studio debate genre was initially inspired by the 1960s television news coverage that captured the zeitgeist of American political campaigns and elections, which featured prominent political figures. The genre has since been adapted by broadcast networks around the world to facilitate politically-charged public discussions that allow ordinary people to pose significant questions and express their concerns or cynicism to the political elites in power. The Big Debate South Africa is a popular televised town hall debate show that began airing in 2009 on eMedia Investment's eNCA and later on the SABC. During its ninth-season run, the show attracted an audience of up to 12 million. The programme is formatted to give South African citizens a voice to hold state leaders to account. Anthea Garman and Herman Wasserman's (2014) research on citizenship and media in a democratic society, asserts that the media's contribution to citizenship is often a way to encourage citizens to exercise their influence over political decisions and dialogue in an overt manner. Through observations and qualitative in-depth interviews, this tightly focused study analysed the third episode of The Big Debate South Africa's ninth season, hosted by journalist and broadcaster Redi Tlhabi. It explored the show's format and discourse to investigate how it creates opportunities for the practice of Susan Bickford's (1996) conception of 'political listening' within the confines of hierarchical binary oppositions ('Us and Them' and 'lay'/'expert'). By deconstructing how civil society organisations, activists and citizens ('lay') interact with the political elites ('experts'), this study chronicled how the show mediates these binary oppositions with an anticipation for them to collectively hear each other out. In examining the show's structure as a participative civic political broadcast talk platform that promotes democratic deliberation, this study ultimately demonstrated the capacity of The Big Debate South Africa to pluralise democratic life in its practice of 'political listening'. While the show advances equality and amplifies marginalised voices, this research also found that these significant practices seemingly only held temporary effects once the cameras shut down.
Keywords: Big Debate -- South Africa; Television talk shows -- South Africa; Citizenship in journalism -- South Africa; Democracy -- South Africa; Mass media and public opinion -- South Africa; Listening Political aspects -- South Africa